Pemberdayaan Masyarakat Berbasis Digital, Kreativitas dan Lingkungan untuk Kelurahan Tirta Siak Berdaya Saing yang Unggul - Putri, Dinda Nurlaila; Nurhasanah, Dilla; Nahta, Raka Dea; Harumi, Avrilia; Azitiya, Azitiya; ayu Syakina, Difa Putri; Rahmadini, Wan Karin; Hasan, Nanda Ismail; Khadaffi, Muhammad Ardhan; Silpandi, Dimas; Mustaqim, Farhan; Hermawan M, Farreliananda; Aurelia, Aprila Fitri; Manik, Scoth Hendric; Alzena, Tania; Putri, Rahma; Ramadhan, Arif; Dewi, Sara; Mardani, Wili; Tinambunan, Wahyul; Travel, Muhammad; Akbar, Qori Yudi; Sandono, Jendi Ade; Ristinnanda, Nia; Siregar, Sri Hilma (Universitas Pahlawan Tuanku Tambusai, 2025)
The Community Service Program (Kuliah Kerja Nyata - KKN) conducted by students of the University of Muhammadiyah Riau in Tirta Siak Village focuses on community empowerment through various integrated programs. The main programs include the development of a village website for transparency, the distribution of chili seeds to support food security, and socialization on anti-bullying and sexual violence. Additionally, a live streaming studio was established to foster creativity and disseminate positive information, while road patching was carried out for infrastructure improvement. Through a participatory approach, this program successfully increased access to information, social awareness, and the competitiveness of MSMEs (Micro, Small, and Medium Enterprises), while also building a foundation for the future development of the village.